The Readiness of E-Government Adoption in Iraq: A Case Study of Al-Muthanna Province - Albadri, Ruwaidah F. (International Journal of Psychosocial Rehabilitation, 2020)
The reinvention of the use of information communication technologies (ICT) and the government services have stimulated new government services. The purpose of this paper is to combine the social and technical aspects of the adoption of e-governance. Little work has been done on e-governance in Iraq and its cities. This study works to fill the gap in previous studies in this field. Data were collected through the work of a paper and electronic questionnaire and distributed to a selected sample in the province of Al-Muthanna where the factors and variables were selected based on the analysis of previous studies and benefit from their results in the design of the questionnaire. The data was then analyzed examined by using SPSS. Using linear regression and preamble, the results revealed significant direct effects of independent factors on the adoption of electronic participation, while intermediate correlation was supported as assumed. In general, the results of this research can help the Iraqi government to adopt the e-participation system, so that the government can perform e-participation processes efficiently and effectively. Future research trends are also given in the end.